Effects of Social Acknowledgment and Interpersonal Shame on Complex Posttraumatic Stress Disorder Symptoms of Sexual Violence Survivors in South Korea - Lee, Ahyeon (Journal of interpersonal violence, 2024)
Sexual violence (SV) survivors face negative social reactions, which can affect their recovery. Based on the socio-interpersonal model of trauma, understanding how societal circumstances impact SV survivors’ mental health is important. This study examined conditional indirect effects of interpersonal shame and social acknowledgment on the relationship between perceived SV event severity and complex post-traumatic stress disorder (CPTSD) symptoms. Cross-sectional data from 157 community-based adults who had previously experienced SV were collected from an online panel. Exploratory factor analysis of the Social Acknowledgment Questionnaire was conducted, followed by conditional indirect analyses using Models 1, 4, and 7 of PROCESS macro. First, results showed that a two-factor model of social acknowledgment consisting of “social disapproval” and “social recognition” was more suitable for this study than a three-factor model predominantly used by Western societies. Second, interpersonal shame partially mediated the relationship between perceived SV event severity and CPTSD symptoms. Third, the conditional indirect effect of social disapproval on the mediating effect of interpersonal shame was significant when the social disapproval level was high. This indicates that the indirect effect of interpersonal shame on CPTSD increases when the social disapproval level is high. This study supported the socio-interpersonal perspective of trauma and suggested that increasing social acknowledgment beyond personal-level intervention would be a critical step for recovery of SV survivors to decrease their interpersonal shame and CPTSD.